STUDI LITERATUR: KONSEP PENGOLAHAN DATA - Angga Wirayuda; Bima Arya Pamungkas; Ilyas Hadi Marta; Azamul Fadhly Noor Muhammad (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Data processing is an essential topic in elementary school mathematics learning because it plays an important role in developing students’ statistical literacy, logical thinking, and data-based decision-making skills. However, various studies indicate that elementary school students still experience difficulties and misconceptions in understanding basic statistical concepts such as mean, median, and mode, as well as in interpreting data presented in tables and diagrams. This study aims to review and synthesize research findings related to the concept of data processing in elementary schools. The research employed a literature study method with a qualitative descriptive approach. Data sources consisted of national and international journal articles relevant to data processing learning at the elementary school level, collected through academic databases and repositories. The data were analyzed using content analysis to identify patterns of learning difficulties, misconceptions, and effective instructional strategies. The results of the literature review show that students’ difficulties are influenced by weak conceptual understanding, procedural-oriented learning, and low learning engagement. Furthermore, contextual learning approaches, the use of instructional media, and student-centered learning models have been proven effective in improving students’ understanding of data processing concepts. This study concludes that meaningful, contextual, and concept-oriented instruction is crucial for enhancing elementary school students’ understanding of data processing and statistical literacy. Keywords: Data Processing, Statistical Literacy, Elementary School Mathematics